From Therapeutic Factors to Mechanisms of Change in the Creative Arts Therapies: A Scoping Review - de Witte, Martina; Orkibi, Hod; Zarate, Rebecca; Karkou, Vicky; Sajnani, Nisha; Malhotra, Bani; Ho, Rainbow Tin Hung; Kaimal, Girija; Baker, Felicity A.; Koch, Sabine C. (Frontiers in Psychology, 2021)
Empirical studies in the creative arts therapies (CATs; i.e., art therapy, dance/movement therapy, drama therapy, music therapy, psychodrama, and poetry/ bibliotherapy) have grown rapidly in the last ten years, documenting their positive impact on a wide range of psychological and physiological outcomes (e.g., stress, trauma, depression, anxiety, and pain). However, it remains unclear how and why the CATs have positive effects, and which therapeutic factors account for these changes. Research that specifically focuses on the therapeutic factors and/or mechanisms of change in CATs is only beginning to emerge. To gain more insight into how and why the CATs influence outcomes, we conducted a scoping review (Nstudies = 67) to pinpoint therapeutic factors specific to each CATs discipline, joint factors of CATs, and more generic common factors across all psychotherapy approaches. This review therefore provides an overview of empirical CATs studies dealing with therapeutic factors and/or mechanisms of change, and a detailed analysis of these therapeutic factors which are grouped into domains. A framework of 19 domains of CATs therapeutic factors is proposed, of which the three domains are composed solely of factors unique to the CATs: “embodiment,” “concretization,” and “symbolism and metaphors.” The terminology used in change process research is clarified, and the implications for future research, clinical practice, and CATs education are discussed.